Interseasonal variation of Chrysodeixis includens (Walker, [1858]) (Lepidoptera: Noctuidae) populations in the Brazilian Savanna - Sabrina Raisa dos Santos; Alexandre Specht; Eduardo Carneiro; Silvana Vieira de Paula-Moraes; Mirna Martins Casagrande (Revista Brasileira de Entomologia)
Abstract Chrysodeixis includens (Walker, [1858]) is currently the main plusiine pest in the Americas, not only because of the damage caused to soybean, but also with several crop species in a broad geographical range. However, its population dynamics is still poorly understood, despite outbreak records that are common across different locations in the Americas. The current study aimed at identifying phenological patterns of C. includens emphasizing its differences among the three years of sampling effort in an intercropping area of the Brazilian Savanna. Thereafter, we tested whether the El Niño size effect, meteorological factors, or soybean, corn and wheat cycles, are better predictors of its monthly abundance. The insects were collected with a light trap during five consecutive nights (repetitions) during 35 new moons. In total, 2026 specimens were collected in all months of the year although not consecutively. Across each year, monthly abundance of C. includens was non-uniform, characterized by sharp population peaks concentrated in the rainy season. These peaks varied from January until March, depending on the year sampled. We found that the local soybean cycle and El Niño effect to significantly influence the species abundance across the entire period of study. These results aid in understanding the species population dynamics and its status as a pest, providing evidence of factors that determine its phenological patterns. Although it presents a very defined phenology, the population dynamics of C. includens varies significantly between years and locations, which demonstrates the importance and need to monitor local populations of larvae and adults for its management.